MRGPRX4 in Cholestatic Pruritus - Yu, Huasheng; Wangensteen, Kirk; Deng, Tong; Li, Yulong; Luo, Wenqin (Seminars in Liver Disease, 2021)
Pruritus (itch) is a debilitating symptom in liver diseases with cholestasis, which severely affects patients' quality of life. Limited treatment options are available for cholestatic itch, largely due to the incomplete understanding of the underlying molecular mechanisms. Several factors have been proposed as pruritogens for cholestatic itch, such as bile acids, bilirubin, lysophosphatidic acid, and endogenous opioids. Recently, two research groups independently identified Mas-related G protein-coupled receptor X4 (MRGPRX4) as a receptor for bile acids and bilirubin and demonstrated its likely role in cholestatic itch. This discovery not only opens new avenues for understanding the molecular mechanisms in cholestatic itch but provides a promising target for developing novel anti-itch treatments. In this review, we summarize the current theories and knowledge of cholestatic itch, emphasizing MRGPRX4 as a bile acid and bilirubin receptor mediating cholestatic itch in humans. We also discuss some future perspectives in cholestatic itch research.
Keywords: MRGRPX4; cholestasis; pruritus